A large-size tin-phosphor bronze rod and its preparation method
By adjusting the chemical composition and microstructure of tin-phosphor bronze rods, increasing the distribution number and size control of Fe3P and Cu3P strengthening phases, reducing the number and size of delta phases, and reasonably regulating the direction and texture, large-scale tin-phosphor bronze rods are solved. The problem of insufficient tensile strength of the material achieves high strength and good plasticity.
Patent Information
- Application Number
- CN202310876570.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-18
AI Technical Summary
The prior art is difficult to significantly improve the tensile strength of large-sized tin-phosphor bronze rods through deformation strengthening and work hardening methods, and it is difficult to achieve the desired high strength through deformation strengthening of large-sized rods.
By adjusting the chemical composition and microstructure of tin-phosphor bronze rods, the distribution number and size of Fe3P and Cu3P strengthened phases are increased to be controlled below 100nm, while reducing the number and size of δ phases, and reasonably adjusting the <111> and <100> directions Distribution of texture.
It has achieved high strength and good plasticity of large-scale tin-phosphor bronze rods, meeting the demand for high-strength materials in aerospace, marine engineering and other fields.
Smart Images

Figure CN116875841B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper alloys, and in particular relates to a large-size tin-phosphor bronze bar and a preparation method thereof. Background Art
[0002] Tin phosphor bronze is a ternary alloy with Cu, Sn and P as the main alloying elements. It has the characteristics of good conductivity, corrosion resistance and high strength. The following bars are mainly used to make precision springs, electrical connectors, terminals, etc. The tensile strength of these small-sized bars can easily reach 600Mpa, or even 1000Mpa; The above large-size bars are usually used to process mechanical parts that bear high loads, such as parts of aircraft, missiles and other aircraft in the aviation field, and pipes and valves in the chemical and marine engineering fields.
[0003] Because tin-phosphorus bronze is a deformation-strengthened copper alloy, high strength is achieved mainly through work hardening with large deformation.
[0004] The Chinese patent with publication number CN114875270A discloses a method for preparing a tin-phosphor bronze alloy, comprising: a tin-phosphor bronze alloy as claimed in claim 1; 2) casting: casting a blank by horizontal continuous casting, wherein the pulling rate is 0.2-1.0 m / min, the pulling pitch is 1-3 mm, the back thrust length is 0.1-0.5 mm, the cooling water pressure is 0.5-0.8 MPa, the cooling water inlet temperature is 15-25°C, the water outlet temperature is 20-40°C, and the casting temperature is controlled at 1190-1220°C; 3) homogenization annealing: homogenizing the blank, the annealing temperature range is 680-720°C, the holding time is 6-10h, and the homogenized blank is quenched after the holding time is reached, and the water entry time after the furnace is controlled within 30s; 4) the first stretching: stretching the blank after homogenization annealing, and the processing rate is controlled at 10-3 5%; after the stretching is completed, the skinning treatment is carried out, and the skinning amount is 0.2-1mm; 5) Intermediate high temperature annealing: the stretched billet is annealed, the annealing temperature range is: 520-600℃, and the holding time is 2-5h; 6) Second stretching: the billet after the intermediate high temperature annealing is stretched, and the second stretching processing rate is controlled at 30-60%; 7) Intermediate low temperature annealing: the billet after the stretching is annealed, the annealing temperature range is: 350-450℃, and the holding time is 3-10h; 8) Finished product stretching: the billet after the intermediate low temperature annealing is stretched, and the finished product stretching is divided into 2-4 passes, and the processing rate of each pass is controlled at: 10-30%, and the total stretching processing rate is 40-70%; 9) Stress relief annealing: the finished bar is subjected to stress relief annealing, and atmosphere protection is carried out, the heating rate is controlled at 5-10℃ / min, the holding temperature is controlled at 150-200℃, and the holding time is 4-12h.
[0005] The above patent achieves the improvement of tensile strength through deformation strengthening and work hardening. However, for large-sized bars, especially The above large-sized bar strength is difficult to achieve the high strength we expect through deformation strengthening. When large-sized bars are stretched at a high processing rate, the metal in the core of the bar is less hardened than the surface metal. To improve the tensile strength of the core of large-sized bars, a higher processing rate is required. The problem is that the tensile stress on the surface metal of the bar exceeds its strength limit and transverse cracks appear. Therefore, the strength of large-sized bars cannot be improved through deformation strengthening and work hardening. Summary of the invention
[0006] The invention provides a large-size tin-phosphor bronze rod with higher strength and better plasticity.
[0007] The invention provides a large-size tin-phosphor bronze rod, which is composed of the following components in weight percentage: Sn: 7-10wt%, P: 0.15-0.35wt%, Fe: 0.03-0.2wt%, Zr: 0.003-0.1wt%, impurity Pb≤0.007wt%, other impurities<0.5wt%, and the balance is Cu;
[0008] The large-size tin phosphor bronze rod comprises Fe3P phase and Cu3P phase, and the distribution quantity of the Fe3P phase is not less than 3000 / mm 2 The distribution number of the Cu3P phase is not less than 1000 / mm 2 ;
[0009] The diameter of the large-size tin phosphor bronze rod is above.
[0010] Furthermore, the large-size tin phosphor bronze rod also includes a δ phase, the size of the δ phase is less than 1 μm, and the distribution number of the δ phase does not exceed 10 / mm 2 .
[0011] Furthermore, the size of the Fe3P phase is less than 100 nm, and the size of the Cu3P phase is less than 60 nm.
[0012] The structure of the large-size tin-phosphor bronze rod provided by the present invention includes Cu3P, Fe3P, Fe2P and δ phase in addition to the matrix phase α phase. Since the mechanical properties of the large-size tin-phosphor bronze rod are affected by Cu3P, Fe3P, Fe2P and δ phase, it is necessary to control the size and distribution amount of Cu3P, Fe3P, Fe2P and δ phase. Cu3P, Fe3P and Fe2P are strengthening phases, which are beneficial to the strength of the alloy. Among them, Fe2P is a granular solid solution strengthening phase at high temperature, and Fe3P is a precipitated network strengthening phase, which is transformed from Fe2P. The strengthening effect of the Fe3P precipitation phase is much better than that of the F2P solid solution phase. The Cu3P phase is also a low-temperature precipitation phase. The strengthening effects of the three strengthening phases are in the order of Fe3P>Cu3P>Fe2P. Therefore, in order to improve the strength of the large-size tin-phosphor bronze rod, it is necessary to regulate the size and distribution amount of the four phases. The regulation direction is: reduce the size of the four phases as much as possible, increase the number of Fe3P phases and the number of Cu3P phases, and reduce the number of Fe2P and δ phases. Therefore, in the present invention, the Fe3P phase size should be controlled below 100nm, and the distribution number should not be less than 3000 / mm 2 ; The size of Cu3P phase should be controlled below 60nm, and the number of distribution should not be less than 1000 / mm 2The δ phase is a brittle phase and a harmful phase in tin-phosphor bronze. It weakens the deformation strengthening effect of tin-phosphor bronze and the plasticity of the alloy. The size and quantity of the δ phase should be minimized. Therefore, in the present invention, the size of the δ phase should be controlled below 1 μm, and the number of distribution should not exceed 10 / mm. 2 .
[0013] Sn: Sn has a strong solid solution strengthening effect in Cu. As the Sn content increases, the strength of tin phosphor bronze increases. When the Sn content is less than 7%, the solid solution strengthening effect of Sn contributes little to improving the strength of the alloy, and thus cannot play a role in pinning dislocations and fixing dislocations. However, as the Sn content increases, Cu and Sn form a hard and brittle δ phase, which is formed by Cu and Sn. 31 Sn8 compounds have a negative impact on improving the strength of tin-phosphor bronze. When the Sn content exceeds 10%, the number of δ phases increases, the size becomes larger, and even the δ phase agglomerates, which will reduce the strength of tin-phosphor bronze. Therefore, in the tin-phosphor bronze alloy of the present invention, the Sn content is controlled in the range of 7-10%.
[0014] P: P and Cu can easily form a coherent and ordered A3B type intermetallic compound Cu3P. When the P content is lower than 0.15%, it is difficult for P to form sufficient Cu3P and Fe3P strengthening phases with Cu and Fe, and the strength of the alloy is improved by second phase precipitation strengthening. When the P content exceeds 0.35%, Cu3P forms a triple eutectic (α+δ+Cu3P) with the α phase and the δ phase, causing the hot brittleness of the alloy, which can easily lead to cracking of the tin-phosphor bronze during hot working or heat treatment. Therefore, the P content in the tin-phosphor bronze of the present invention does not exceed 0.35%.
[0015] Fe: The solubility of Fe in tin-phosphor bronze is extremely small. Trace amounts of Fe mainly form Fe2P and Fe3P phases with P. At high temperatures, Fe and P mainly form Fe2P, while at low temperatures, they are easy to form Fe3P. Through aging treatment, the granular Fe2P can be transformed into Fe3P with a network structure, which has a better strengthening effect.
[0016] Zr: Zr is a grain boundary strengthening element. When added to tin-phosphor bronze, it can refine the alloy grains, strengthen the alloy grain boundaries, and make the crystal structure of the ingot dense. Zr is enriched in the liquid phase at the crystallization front, which reduces the melting point of the components at the solid-liquid interface front, promotes the formation of component supercooling, refines the α-Cu dendrite arms, and reduces the secondary crystal arm spacing; and ZrO formed by Zr and oxygen hinders the growth of α-Cu crystals and helps the branching and refinement of α-Cu dendrites. When the amount of Zr added to tin-phosphor bronze exceeds 0.1%, the grain refinement effect becomes worse.
[0017] Furthermore, the microstructure of the large-size tin-phosphor bronze rod includes <111> Directional texture and <100> Directional texture, parallel to the tensile direction of large-size tin-phosphor bronze bars <111> Directional texture area S <111> The proportion of the total texture area parallel to the tensile direction of the rod is 60-75%. <100> Directional texture area S <100> The proportion of the total texture area parallel to the stretching direction of the rod is 25-40%.
[0018] The microstructure of the tin phosphor bronze rod of the present invention has <111> and <100> Two directional textures, <111> and <100> Directional textures include: textures parallel to the tensile direction of the rod and textures at a certain angle to the tensile direction. The textures parallel to the tensile direction of the rod have the greatest effect on improving the strength of the rod. <111> The effect of directional texture on improving the strength of tin phosphor bronze rods is stronger than <100> Directional texture, and <100> The effect of directional texture on improving the plasticity of tin phosphor bronze rods is better than <111> Therefore, in the present invention, by rationally regulating <111> and <100> The distribution of directional texture makes the obtained rod have higher strength, among which the <111> Directional texture area S <111> The proportion of the total texture area parallel to the stretching direction of the rod should be controlled at 60-75%. <100> Directional texture area S <100> The proportion of the total texture area parallel to the stretching direction of the rod is 25-40%.
[0019] The present invention also provides a method for preparing a large-size tin-phosphor bronze rod, comprising:
[0020] (1) preparing ingredients, smelting and casting the large-size tin-phosphor bronze rod according to the weight percentage of each component to obtain a master alloy ingot;
[0021] (2) subjecting the master alloy ingot obtained in step (1) to high temperature annealing, wherein the high temperature annealing process comprises: maintaining the temperature at 650-750° C. for 4-8 hours, then raising the temperature to 780-900° C. after 10-40 minutes and maintaining the temperature for 5-20 minutes;
[0022] (3) water-sealing extrusion of the master alloy ingot obtained in step (2), wherein the extrusion speed is 2-11 mm / s, the extrusion ratio is 10-40, and the water temperature is less than 50° C.;
[0023] (4) stretching the master alloy extrusion billet obtained in step (3) for 1 to 4 times to obtain a rod of set specifications, wherein the total processing rate of the stretching process is ≥ 20%;
[0024] (5) performing aging annealing on the bar obtained in step (4), wherein the aging annealing process is: heating from room temperature to 390-450°C over 20-40 minutes, keeping the temperature for 90-150 minutes, then cooling to 320-360°C over 20-45 minutes, and keeping the temperature for 60-120 minutes;
[0025] (6) The rod obtained in step (5) is stretched again for 1 to 3 times to obtain a rod of finished product specifications, and the total processing rate of the stretching process is 10 to 25%;
[0026] (7) performing low temperature annealing on the rod obtained in step (6), wherein the low temperature annealing process is: raising the temperature from room temperature to 170-260° C. over 30-60 minutes, and keeping the temperature for 120-300 minutes;
[0027] (8) The rod obtained in step (7) is straightened to obtain a large-sized tin-phosphor bronze rod.
[0028] The invention utilizes the high temperature annealing process of 650-750 DEG C for 4-8 hours to reduce the delta phase distributed between the dendrites of the tin-phosphor bronze, thereby improving the plasticity of the finally obtained tin-phosphor bronze rod.
[0029] The present invention provides a water seal extrusion with a suitable extrusion ratio. When the extrusion ratio is lower than 10, the extruded billet still retains the cast structure of the ingot due to the low degree of extrusion deformation, and the material properties deteriorate. Since the extruded billet of the present invention has large specifications, there is no problem of being unable to extrude due to an extrusion ratio that is too large. After the extruded billet is extruded from the mold, it immediately enters the water seal tank for online solid solution using waste heat. The water temperature of the whole process should be less than 50°C. The higher the water temperature, the lower the cooling intensity and the worse the solid solution effect. The water seal extrusion provided by the present invention has two purposes. One is to promote the complete dissolution of the second phases of Cu3P and Fe2P into the alloy matrix, so as to prepare for the subsequent precipitation of small-sized Cu3P strengthening phases by aging; the other is to avoid the growth of recrystallized grains during extrusion through extremely rapid cooling, thereby achieving fine grain strengthening and improving the plasticity of the billet, providing a basis for high processing rate stretching in the next process.
[0030] The purpose of the first stretching provided by the present invention is to increase the dislocation density in the alloy, promote the dispersion and precipitation of the Cu3P and Fe3P second phases during aging annealing, reduce the size of the second phase, and increase the area ratio.
[0031] The purpose of the aging annealing provided by the present invention is to promote the precipitation of Cu3P and Fe3P second phases from the alloy matrix, thereby improving the strength of the alloy. Since the peak precipitation temperatures of Cu3P and Fe3P phases are different, the peak precipitation temperature of Cu3P phase is around 340°C, and the peak precipitation temperature of Fe3P phase is around 420°C. Therefore, the tin-phosphor bronze alloy of the present invention adopts a segmented aging process, and the first stage is rapidly heated to 390-450°C after 20-40 minutes, and then kept warm for 90-150 minutes; the second stage is cooled to 320-360°C after 20-45 minutes, and then kept warm for 60-120 minutes.
[0032] The second stretching provided by the present invention has two purposes: one is to improve the strength of the alloy through deformation strengthening; the other is to control the parallel to the stretching direction of the bar through the stretching processing rate. <111> and <100> The proportion of directional texture is due to the increase in processing rate. <111> The direction ratio will increase, and <100> The proportion of directional texture will decrease, and the number of stretching passes will affect the direction of the texture. Under the condition that the total processing rate remains unchanged, the fewer the passes, the easier it is to form a texture parallel to the stretching direction of the rod. However, as the number of passes decreases, it is difficult for the rod to be stretched and deformed. On the contrary, cracks will form on the surface of the rod due to the excessive processing rate of the passes.
[0033] The process parameters of low temperature annealing provided by the present invention are combined with the content of Sn to further improve the strength of tin phosphor bronze. Under the action of low temperature and long time, due to the comprehensive effect of the segregation of Sn atoms of appropriate content on the stacking fault plane and orderly strengthening, the dislocations inside the material are redistributed and the number of movable dislocations is reduced. Both annealing temperature and time are very important. If the annealing temperature is too low, the dislocations will not be redistributed. If the annealing temperature is too high and exceeds the starting recrystallization temperature of the alloy, not only will the strength of the alloy not be improved, but the strength of the alloy will be reduced due to the occurrence of recrystallization.
[0034] Furthermore, the specific steps of step (1) are:
[0035] According to the weight percentage of each component of the large-size tin-phosphor bronze rod, tin ingot, Cu-P master alloy and Cu-Fe master alloy are smelted at a smelting temperature of 1100-1280°C. When the contents of Sn, P and Fe reach the set range, Cu-Zr master alloy is added after melting for smelting;
[0036] The smelted alloy is cast by a vertical semi-continuous casting method or a horizontal continuous casting method to obtain a master alloy ingot.
[0037] Furthermore, the smelted alloy is cast by a vertical semi-continuous casting method or a horizontal continuous casting method, and the casting process is as follows:
[0038] The casting temperature is 1140-1280℃, the cooling water inlet temperature is 20-35℃, the cooling water pressure is 0.2-0.5Mpa, and the cooling water flow rate is 10-18m 3 / h, the outlet water temperature is 25-45℃, and the pulling speed is 40-100mm / min.
[0039] Furthermore, the master alloy ingot obtained in step (1) is a dendrite, and the distance between the dendrites is 5-15 μm. The smaller the distance between the dendrites, the finer the structure, the smaller the size of the δ phase distributed between the dendrites, and the easier it is to eliminate the δ phase when the ingot is subjected to high temperature annealing.
[0040] Furthermore, the grain size of the master alloy ingot obtained in step (3), i.e., the tin-phosphor bronze extruded billet, is controlled to be below 0.030 mm. Because the smaller the grain size, the more grain boundaries there are, and the more grains in different orientations there are, the greater the resistance to plastic deformation, and thus the higher the strength of the alloy.
[0041] Furthermore, in the recrystallized grains of the master alloy extrusion blank obtained in step (3), that is, the twin area of the tin-phosphor bronze extrusion blank must reach 50-70% of the total grain area. This is because after the twins appear, the twin boundaries will play a hardening role, but the twin boundaries will reduce the plasticity of the alloy. The tin-phosphor bronze alloy of the present invention needs to maintain good plasticity while achieving high strength. The purpose is to absorb part of the energy when the material is subjected to external force, avoid brittle cracks inside the material, and improve the durability of the parts.
[0042] Furthermore, the mechanical properties of large-size tin-phosphor bronze bars with a diameter of more than Ф40mm are shown in Table 1:
[0043] Table 1 Mechanical properties requirements for large-size tin-phosphor bronze bars
[0044] Specification range mm Tensile strengthMpa Elongation A50% 40-50 600 8 50-60 540 12 >60 480 16
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) Since the strengthening phases in the large-sized tin-phosphorus bronze rod provided by the present invention, namely the Fe3P phase and the Cu3P phase, are distributed in large quantities in the large-sized tin-phosphorus bronze rod, the large-sized tin-phosphorus bronze rod has higher strength.
[0047] (2) The strengthening phases in the large-sized tin-phosphorus bronze rod provided by the present invention, namely the Fe3P phase and the Cu3P phase, are relatively small in size, so that the strengthening phases can be dispersed in the matrix, thereby improving the strength of the large-sized tin-phosphorus bronze rod.
[0048] (3) The size of the δ phase in the large-sized tin-phosphorus bronze rod provided by the present invention is relatively small, and the distribution amount in the large-sized tin-phosphorus bronze rod is relatively small, which reduces the influence of the brittle δ phase on the strength of the large-sized tin-phosphorus bronze rod, thereby improving the strength of the large-sized tin-phosphorus bronze rod.
[0049] (4) The large-size tin-phosphor bronze rod provided by the present invention has a <111> The texture area in the directional direction accounts for a higher proportion of the total texture area parallel to the tensile direction of the rod, thereby improving the strength of large-size tin-phosphorus bronze rods.
[0050] (5) The present invention provides a method for preparing large-sized tin-phosphor bronze rods. The method can be used to prepare large-sized tin-phosphor bronze rods with relatively high strength, wherein the strengthening phase is completely dissolved in the alloy matrix by a water seal extrusion method, so as to prepare for the subsequent precipitation of small-sized and large-volume strengthening phases by aging. The Cu3P and Fe3P phases are precipitated from the matrix by staged aging annealing treatments, and the number of movable dislocations is reduced by the combined effect of low-temperature annealing and Sn content, thereby further increasing the strength of the large-sized tin-phosphor bronze rods. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a metallographic structure photograph of a large-sized tin-phosphor bronze rod prepared in Example 1 of the present invention;
[0052] Figure 2 This is a metallographic photograph of the large-size tin-phosphor bronze rod prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0053] The present invention aims at the low tensile strength of the current large-size tin-phosphor bronze bars with diameters of more than 40 mm, which cannot meet the requirements of aerospace and marine engineering for high-strength materials. The present invention designs and develops a large-size high-strength tin-phosphor bronze bar to solve the shortcomings of the prior art and meet the requirements of special fields for high-strength materials. The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0054] The present invention provides 4 embodiments and 2 comparative examples, and the specific components are shown in Table 2.
[0055] Example 1
[0056] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:
[0057] 1) Melting and casting: according to the required ingredients, add electrolytic plate, tin ingot and Cu-P master alloy to the induction furnace for melting in sequence. The melting temperature is 1100-1280℃. After all the metals are melted, the contents of Sn, P and impurity Pb are tested to be qualified, and then Cu-Zr master alloy is added. After the alloy composition is tested again and qualified, it is transferred to the holding furnace. The ingot is cast by the vertical semi-continuous casting method. The ingot diameter is Casting temperature: 1170-1210℃, cooling water inlet temperature: 22-25℃, cooling water pressure: 0.4Mpa, cooling water flow rate: 15m 3 / h, water outlet temperature: 30-35℃, pulling speed: 75mm / min.
[0058] 2) High temperature heating: It is divided into two stages. The first stage heating temperature is 700℃, and the insulation time after reaching the temperature is 6h; the second stage heating temperature is 860-880℃. It takes 25min to heat to this temperature based on the first stage temperature, and then keep it for 15min before extrusion.
[0059] 3) Water seal extrusion: extrusion billet specifications: Extrusion speed: 4-8mm / s, extrusion ratio: 13. After the extruded billet is extruded from the die, it immediately enters the water seal tank for online solid solution using the residual heat, and the water temperature is 17-42℃.
[0060] 4) Stretching: After pickling, the extruded blank is stretched continuously in 3 steps to the bottom specification Mold matching process: Processing rate: 27.43%.
[0061] 5) Aging annealing: A staged aging process is adopted. The first stage is to quickly heat up to 370°C in 25 minutes and then keep it at this temperature for 120 minutes. The second stage is to cool down to 350°C in 30 minutes and then keep it at this temperature for 90 minutes.
[0062] 6) Stretching: After aging annealing, the wire billet is stretched twice to the finished product specifications Mold matching process: The processing rate is controlled at 16.63%.
[0063] 7) Low temperature annealing: Annealing temperature: 200°C, time from room temperature to this temperature: 30 minutes, holding time: 240 minutes.
[0064] 8) Straightening: Straightening on a two-roller straightening machine.
[0065] 9) Inspection.
[0066] like Figure 1 As shown, the grain size is uniform, the average grain size is 0.020 mm, the small black dots are δ phase, and the average size of δ phase is 0.6 μm.
[0067] Example 2
[0068] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:
[0069] 1) Melting and casting: according to the required ingredients, add electrolytic plate, tin ingot and Cu-P master alloy to the induction furnace for melting in sequence. The melting temperature is 1100-1280℃. After all the metals are melted, the contents of Sn, P and impurity Pb are tested and qualified, and then Cu-Zr master alloy is added. After the alloy composition is tested again and qualified, it is transferred to the holding furnace. The horizontal continuous casting method is used to cast the ingot. The ingot diameter is Casting temperature: 1180-1220℃, cooling water inlet temperature: 26-29℃, cooling water pressure: 0.38Mpa, cooling water flow rate: 13m 3 / h, water outlet temperature: 32-36℃, pulling speed: 80mm / min.
[0070] 2) High temperature heating: It is divided into two stages. The first stage heating temperature is 680℃, and the insulation time after reaching the temperature is 7h; the second stage heating temperature is 840-870℃. It takes 25min to heat to this temperature based on the first stage temperature, and then keep it warm for 15min before extrusion.
[0071] 3) Water seal extrusion: extrusion billet specifications: Extrusion speed: 4.2-7.7mm / s, extrusion ratio: 15.3. After the extruded billet is extruded from the die, it immediately enters the water seal tank for online solid solution using the residual heat, and the water temperature is: 21-46℃.
[0072] 4) Stretching: After pickling, the extruded blank is stretched continuously in 3 steps to the bottom specification Mold matching process: Processing rate: 25.78%.
[0073] 5) Aging annealing: A staged aging process is adopted. The first stage is to quickly heat up to 420°C in 25 minutes and then keep it warm for 100 minutes; the second stage is to cool down to 330°C in 35 minutes and then keep it warm for 120 minutes.
[0074] 6) Stretching: After aging annealing, the wire billet is stretched 3 times to the finished product specifications Mold matching process: The processing rate is controlled at 20.28%.
[0075] 7) Low temperature annealing: Annealing temperature: 230°C, time from room temperature to this temperature: 30 minutes, holding time: 120 minutes.
[0076] 8) Straightening: Straightening on a two-roller straightening machine.
[0077] 9) Inspection.
[0078] Example 3
[0079] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:
[0080] 1) Melting and casting: according to the required ingredients, add electrolytic plate, tin ingot and Cu-P master alloy to the induction furnace for melting in sequence. The melting temperature is 1100-1280℃. After all the metals are melted, the contents of Sn, P and impurity Pb are tested and qualified, and then Cu-Zr master alloy is added. After the alloy composition is tested again and qualified, it is transferred to the holding furnace. The horizontal continuous casting method is used to cast the ingot. The ingot diameter is Casting temperature: 1200-1240℃, cooling water inlet temperature: 18-23℃, cooling water pressure: 0.35Mpa, cooling water flow: 12m 3 / h, water outlet temperature: 22-25℃, pulling speed: 60mm / min.
[0081] 2) High temperature heating: It is divided into two stages. The first stage heating temperature is 750℃, and the insulation time after reaching the temperature is 5h; the second stage heating temperature is 800-850℃. It takes 15min to heat to this temperature based on the first stage temperature, and then keep it for 10min before extrusion.
[0082] 3) Water seal extrusion: extrusion billet specifications: Extrusion speed: 4-7mm / s, extrusion ratio: 11.5. After the extruded billet is extruded from the die, it immediately enters the water seal tank for online solid solution using the residual heat, and the water temperature is: 25-42℃.
[0083] 4) Stretching: After pickling, the extruded blank is stretched continuously in 3 steps to the bottom specification Mold matching process: Processing rate: 24.89%.
[0084] 5) Aging annealing: A staged aging process is adopted. In the first stage, the temperature is quickly raised to 450°C in 25 minutes and then kept at this temperature for 90 minutes. In the second stage, the temperature is lowered to 320°C in 35 minutes and then kept at this temperature for 90 minutes.
[0085] 6) Stretching: After aging annealing, the wire billet is stretched twice to the finished product specifications Mold matching process: The processing rate is controlled at 14.79%.
[0086] 7) Low temperature annealing: Annealing temperature: 250°C, time from room temperature to this temperature: 45 minutes, holding time: 180 minutes.
[0087] 8) Straightening: Straightening on a two-roller straightening machine.
[0088] 9) Inspection.
[0089] Example 4
[0090] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:
[0091] 1) Melting and casting: according to the required ingredients, add electrolytic plate, tin ingot and Cu-P master alloy to the induction furnace for melting in sequence. The melting temperature is 1100-1280℃. After all the metals are melted, the contents of Sn, P and impurity Pb are tested and qualified, and then Cu-Zr master alloy is added. After the alloy composition is tested again and qualified, it is transferred to the holding furnace. The horizontal continuous casting method is used to cast the ingot. The ingot diameter is Casting temperature: 1200-1240℃, cooling water inlet temperature: 28-31℃, cooling water pressure: 0.42Mpa, cooling water flow rate: 18m 3 / h, water outlet temperature: 36-40℃, pulling speed: 60mm / min.
[0092] 2) High temperature heating: It is divided into two stages. The first stage heating temperature is 720℃, and the insulation time after reaching the temperature is 6h; the second stage heating temperature is 780-820℃. It takes 10min to heat to this temperature based on the first stage temperature, and then keep it for 15min before extrusion.
[0093] 3) Water seal extrusion: extrusion billet specifications: Extrusion speed: 4-7.5mm / s, extrusion ratio: 10.6. After the extruded billet is extruded from the die, it immediately enters the water seal tank for online solid solution using the residual heat, and the water temperature is: 29-50℃.
[0094] 4) Stretching: After pickling, the extruded blank is stretched continuously in two passes to the bottom specification Mold matching process: Processing rate: 21.74%.
[0095] 5) Aging annealing: A staged aging process is adopted. The first stage is to quickly heat up to 430°C in 25 minutes and then keep it at this temperature for 90 minutes; the second stage is to cool down to 350°C in 30 minutes and then keep it at this temperature for 90 minutes.
[0096] 6) Stretching: After aging annealing, the wire billet is stretched once more to the finished product specifications Mold matching process: The processing rate is controlled at 11.26%.
[0097] 7) Low temperature annealing: Annealing temperature: 180°C, time from room temperature to this temperature: 30 minutes, holding time: 300 minutes.
[0098] 8) Straightening: Straightening on a two-roller straightening machine.
[0099] 9) Inspection.
[0100] Comparative Example 1
[0101] The chemical composition was controlled according to Example 1, and the Ø42 mm bar was produced by the conventional process route of "melting → horizontal continuous casting Ø54 → homogenization annealing (680°C / 6h) → multi-pass continuous stretching Ø42 → straightening → inspection". The organization and performance results are listed in Table 3. The metallographic structure is as follows Figure 2 As shown, the grains are relatively coarse, with an average grain size of 0.040 mm, and the black dots are δ phases with an average size of 4.3 μm.
[0102] Comparative Example 2
[0103] Commercially available QSn8-0.3 Rod.
[0104] The following tests were performed on the microstructures of the four embodiments and two comparative examples, and the results are recorded in Table 3.
[0105] Performance Analysis:
[0106] Grain size: The metallographic specimens were prepared in accordance with GB / T 13298, and the grain size was measured by the comparison method specified in GB / T 6394-2017 (Method for determination of average grain size of metals), that is, the grain size was evaluated by comparing with the standard rating chart;
[0107] The phase proportion, phase size, and phase distribution quantity were observed under a scanning electron microscope;
[0108] Texture area ratio: observed and measured using a scanning electron microscope backscattered electron diffraction (EBSD) device.
[0109] Tensile strength Rm and elongation A50: tested in accordance with GB / T228.1-2021 "Tensile test of metallic materials Part 1: Room temperature test method".
[0110] The following performance tests were performed on the four embodiments and two comparative examples, and the results are recorded in Table 4.
[0111] Table 2 Chemical composition of Examples 1-4 and Comparative Examples 1-2
[0112]
[0113]
[0114] Table 3 Grain size, phase size, number of distribution per unit area, and texture area ratio of Examples 1-4 and Comparative Examples 1-2
[0115]
[0116] Table 4 Tensile strength and elongation of Examples 1-4 and Comparative Examples 1-2
[0117]
Claims
1. A large-size tin-phosphor bronze bar, characterized in that: It is composed of the following components in weight percentage: Sn: 7-10wt%, P: 0.15-0.35wt%, Fe: 0.03-0.2wt%, Zr: 0.003-0.1wt%, impurity Pb≤0.007wt%, other impurities<0.5wt%, and the balance is Cu; The large-size tin phosphor bronze rod includes Fe3P phase and Cu3P phase, and the distribution number of the Fe3P phase is not less than 3000 / mm 2 The distribution number of the Cu3P phase is not less than 1000 / mm 2 ; The diameter of the large-size tin-phosphor bronze rod is greater than φ40 mm.
2. The large-size tin-phosphor bronze rod according to claim 1 is characterized in that: The large-size tin phosphor bronze rod also includes a δ phase, the size of the δ phase is less than 1 μm, and the distribution number of the δ phase does not exceed 10 / mm 2 .
3. The large-size tin-phosphor bronze bar according to claim 1 is characterized in that: The size of the Fe3P phase is less than 100 nm, and the size of the Cu3P phase is less than 60 nm.
4. The large-size tin-phosphor bronze bar according to claim 1 is characterized in that: The microstructure of the large-size tin phosphor bronze rod includes <111> Directional texture and <100> Directional texture; Among them, parallel to the tensile direction of the large-size tin phosphor bronze rod <111> Directional texture area S <111> occupy <111> The proportion of the total area of directional texture is 60-75%; Parallel to the stretching direction of the bar <100> Directional texture area S <100> occupy <100> The proportion of the total area of directional texture is 25-40%.
5. A method for preparing a large-size tin-phosphor bronze rod according to any one of claims 1 to 4, characterized in that: include: (1) preparing, smelting and casting the large-size tin-phosphor bronze rod according to the weight percentage of each component to obtain a master alloy ingot; (2) subjecting the master alloy ingot obtained in step (1) to high temperature annealing, wherein the high temperature annealing process comprises: maintaining the temperature at 650-750° C. for 4-8 hours, then raising the temperature to 780-900° C. after 10-40 minutes and maintaining the temperature for 5-20 minutes; (3) water-sealing extrusion of the master alloy ingot obtained in step (2), wherein the extrusion speed is 2-11 mm / s, the extrusion ratio is 10-40, and the water temperature is less than 50° C.; (4) stretching the master alloy extrusion blank obtained in step (3) for 1 to 4 times to obtain a rod of set specifications, wherein the total processing rate of the stretching process is ≥ 20%; (5) performing aging annealing on the bar obtained in step (4), wherein the aging annealing process is: heating from room temperature to 390-450°C over 20-40 minutes, keeping the temperature for 90-150 minutes, then cooling to 320-360°C over 20-45 minutes, and keeping the temperature for 60-120 minutes; (6) The rod obtained in step (5) is stretched again for 1 to 3 times to obtain a rod of finished product specifications, and the total processing rate of the stretching process is 10 to 25%; (7) performing low temperature annealing on the rod obtained in step (6), wherein the low temperature annealing process is: raising the temperature from room temperature to 170-260° C. over 30-60 minutes, and keeping the temperature for 120-300 minutes; (8) The rod obtained in step (7) is straightened to obtain a large-sized tin-phosphor bronze rod.
6. The method for preparing large-size tin-phosphor bronze rods according to claim 5, characterized in that: The specific steps of step (1) are: According to the weight percentage of each component of the large-size tin-phosphor bronze rod, tin ingot, Cu-P master alloy and Cu-Fe master alloy are melted at a melting temperature of 1100-1280°C. When the contents of Sn, P and Fe reach the set range, Cu-Zr master alloy is added for melting; The smelted alloy is cast by a vertical semi-continuous casting method or a horizontal continuous casting method to obtain a master alloy ingot.
7. The method for preparing large-size tin-phosphor bronze rods according to claim 6, characterized in that: The smelted alloy is cast by a vertical semi-continuous casting method or a horizontal continuous casting method, and the casting process is as follows: The casting temperature is 1140-1280℃, the cooling water inlet temperature is 20-35℃, the cooling water pressure is 0.2-0.5Mpa, and the cooling water flow rate is 10-18m 3 / h, the outlet water temperature is 25-45℃, and the pulling speed is 40-100mm / min.
8. The method for preparing large-size tin-phosphor bronze rods according to claim 5, characterized in that: The master alloy ingot obtained in step (1) is dendrites, and the spacing between the dendrites is 5-15 μm.
9. The method for preparing large-size tin-phosphor bronze rods according to claim 5, characterized in that: The grain size of the master alloy ingot obtained in step (3) is controlled to be below 0.030 mm.
10. The method for preparing large-size tin-phosphor bronze rods according to claim 5, characterized in that: In the recrystallized grains of the master alloy extrusion blank obtained in step (3), the twin area must account for 50-70% of the total grain area.
Citation Information
Patent Citations
Tin-phosphor bronze alloy and preparation method thereof
CN114875270A
Processing method of miniature square rod of tin-phosphor bronze
CN112795809A
Short-process heat treatment method for CuNiSn alloy bar
CN114351063A